Determination of a safe trajectory with the use of an ant algorithm and consideration of the ship’s maneuvering characteristic - Lazarowska, A. (Scientific Journal of Gdynia Maritime University, 2017)
The article presents a proposal for solving the problem of determining a ship’s safe trajectory using one of the stochastic optimization methods, which is an ant algorithm. In the process of ship’s safe path planning all of the most important requirements and limitations were taken into account, which include the International Regulations for Preventing Collisions at Sea (COLREGs), static (lands, shoals) and dynamic (target ships) obstacles, a safe distance between ships, weather conditions (visibility) and dynamic properties of the ship. The dynamics of an own ship were taken into account in the form of maneuver time, the value of which is indicated by the maneuvering characteristic of a vessel.